Air Source Heat Pumps field studies: A systematic literature review. (December 2020) - Carroll, P.; Chesser, M.; Lyons, P.
Abstract: The electrification of home heating is proposed as a low carbon solution in climate change action plans. It is therefore important to understand the energy efficiency and capability of heat pumps when deployed in the homes of end users. This paper presents a systematic literature review of Air Source Heat Pumps (ASHP) field studies. The papers are reviewed with respect to the field study focus, and analysed in terms of the field study design, and the analysis methodologies applied to the gathered data. The review finds three main areas of focus: defrosting management, ASHP system management, and ASHPs as smart grid demand response components. The review also identifies what ASHP data is publicly available to assist other researchers in building, testing and analysing ASHP efficiency models. Finally, future research topics on the use of ASHPs in home heating are identified. Highlights: Systematic Literature Review of ASHP Field Trials. Three key themes identified: defrosting, whole ASHP system management, and ASHPs as smart grid components. Variable range of Coefficient of Performance values in field trials.